Polyurethane hot melt adhesive based on Diels-Alder reaction. (July 2020) - Wu, Meiyin; Liu, Yuan; Du, Pengfei; Wang, Xinling; Yang, Bin
Abstract: Traditional hot melt adhesives are thermoplastic resins with non-covalent hydrogen bonds. In this letter, a polyurethane hot melt adhesive (CDI-PUR-DA) was synthesized via introducing thermally reversible covalent Diels-Alder adducts into the polyurethane main chain. Results from hydrogen nuclear magnetic resonance (NMR) analysis and an assessment of rheological properties demonstrated that CDI-PUR-DA exhibited a much lower viscosity than a traditional hot melt adhesive. The viscosity of the polyurethane decreased to 4 Pa s at 110 °C due to rupture of Diels-Alder adducts. However, the viscosity returned to its initial value on cooling due to the regeneration of the Diels-Alder adducts. This approach provides a new method for preparing hot melt adhesives.